[tex]\begin{cases}{\mathrm D}^2x-{\mathrm D}y=e^{2t}-6t\\{\mathrm D}x+{\mathrm D}y=y-x+3e^{2t}\end{cases}[/tex]
Adding the two ODEs gives
[tex]{\mathrm D}^2x+{\mathrm D}x=y-x+4e^{2t}-6t[/tex]
Differentiating once gives
[tex]{\mathrm D}^3x+{\mathrm D}^2x={\mathrm D}y-{\mathrm D}x+8e^{2t}-6[/tex]
[tex]{\mathrm D}^3x+{\mathrm D}^2x-{\mathrm D}y+{\mathrm D}x=8e^{2t}-6[/tex]
The first ODE lets you simplify this a bit:
[tex]{\mathrm D}^3x+e^{2t}-6t+{\mathrm D}x=8e^{2t}-6[/tex]
[tex]{\mathrm D}^3x+{\mathrm D}x=7e^{2t}+6t-6[/tex]
Let [tex]z={\mathrm D}x[/tex], so that [tex]{\mathrm D}^2z={\mathrm D}^3x[/tex], and reduce the order of the ODE to get
[tex]{\mathrm D}^2z+z=7e^{2t}+6t-6[/tex]
Solving this ODE for [tex]z[/tex] shouldn't be a problem for you; you would find that
[tex]z=C_1\cos t+C_2\sin t+\dfrac75e^{2t}+6t-6[/tex]
Since [tex]z={\mathrm D}x[/tex], integrating once with respect to [tex]t[/tex] gives the general solution for [tex]x[/tex]:
[tex]x=C_1\sin t-C_2\cos t+\dfrac7{10}e^{2t}+3t^2-6t+C_3[/tex]
Now plug in the second derivative of this solution into the first ODE to find another ODE in [tex]y[/tex] alone.
[tex]{\mathrm D}^2x=-C_1\sin t+C_2\cos t+\dfrac{14}5e^{2t}+6[/tex]
[tex]-C_1\sin t+C_2\cos t+\dfrac{14}5e^{2t}+6-{\mathrm D}y=e^{2t}-6t[/tex]
[tex]{\mathrm D}y=\dfrac95e^{2t}+6t+6-C_1\sin t+C_2\cos t[/tex]
Integrate with respect to [tex]t[/tex] and you get
[tex]y=\dfrac9{10}e^{2t}+3t^2+6t+C_1\cos t+C_2\sin t+C_3[/tex]